Strengthening the Economy through Empowering Grape Farmers in Duyu Village - Hapsa, Hapsa; Akhlakiani, Luthfia Syahida; Hatta, Ikhtiar; Bakari, Yulianti; Badollahi, Muhammad Zainuddin (Journal of Universal Community Empowerment Provision, 2023)
The natural disaster that occurred in 2018 in Palu City had an impact on the economic condition of the community. Almost all regions felt this impact. One of the areas also affected is Duyu Village. This is one of the reasons for community empowerment through grape farming. The aim of this empowerment is to encourage people to create new jobs after natural disasters which cause a downturn in the community's economy. The method used in the empowerment process starts with mapping, local asset mobilization, monitoring and evaluation. The results of the empowerment carried out in Duyu Village were able to optimize local assets in the village and strengthen the community's economy after experiencing an economic downturn due to natural disasters.